2022
DOI: 10.1021/jacs.2c05779
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Computational Studies Reveal the Importance of Axial Ligand for Oxygen Reduction Reaction on Fe–N–C Materials

Abstract: The systematic improvement of Fe–N–C materials for fuel cell applications has proven challenging, due in part to an incomplete atomistic understanding of the oxygen reduction reaction (ORR) under electrochemical conditions. Herein, a multilevel computational approach, which combines ab initio molecular dynamics simulations and constant potential density functional theory calculations, is used to assess proton-coupled electron transfer (PCET) processes and adsorption thermodynamics of key ORR intermediates. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 108 publications
1
49
0
Order By: Relevance
“…Nonetheless, our main focus is on the geometry of Pt n clusters and its dependence on the applied potential, rather than on the specific electrolyte–electrode interaction, and we expect that the conclusions extracted from this work will hold when applying more elaborate electrochemical models. In this regard, we highlight that modeling the electrochemical reconstruction of interfaces is very challenging, and new theoretical methods continue to be developed. …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, our main focus is on the geometry of Pt n clusters and its dependence on the applied potential, rather than on the specific electrolyte–electrode interaction, and we expect that the conclusions extracted from this work will hold when applying more elaborate electrochemical models. In this regard, we highlight that modeling the electrochemical reconstruction of interfaces is very challenging, and new theoretical methods continue to be developed. …”
Section: Introductionmentioning
confidence: 99%
“…13 However, the coadsorbing species would reduce the activity of pyrrolic FeN 4 C. Upon the acceptance of this work, we noticed the following papers published very lately. Hutchison et al 46 demonstrated the effect of axial ligation on ORR by multilevel computations. Specifically, Ni et al 47 found that the active site of Fe−N−C catalysts for ORR is the iron site coordinated with pyrrolic N by Mossbauer spectroscopy, which is consistent with our computations.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…We determined the proton-coupled redox potentials for GCC-phenazine using the constant potential strategy discussed in previous work of our group and others. ,, In this approach, the grand potentials are calculated as a function of applied potential E for the reactant and product states of a PCET reaction. The change in free energy for a reaction within the grand canonical approach is given as the difference between the product grand potential, Ω P ( E ), and the reactant grand potential, Ω R ( E ): normalΔ normalΩ ( E ) = normalΩ normalP ( E ) normalΩ normalR ( E ) …”
mentioning
confidence: 99%
“…In this work, we investigate PCET at GCC-phenazine, shown in Figure , in the presence of heteroatom dopants and defects on the graphitic carbon surface. The changes in chemical reactivity are tracked by computing the proton-coupled redox potential, E PCET , using a constant potential approach rooted in the grand canonical ensemble. ,, The variations in E PCET are explored in connection with changes in the density of states (DOS) of GCC-phenazine upon both electron and proton transfer. The electronic states directly involved in PCET are shown to be related to the corresponding electronic states of molecular phenazine, corroborating the quasi-molecular character of the GCC site.…”
mentioning
confidence: 99%
See 1 more Smart Citation